IMPROVED REPRODUCTIVE PERFORMANCE OF CROSSBRED CATTLE IN PURI DISTRICT OF ODISHA FOLLOWING SUPPLEMENTATION OF AREA SPECIFIC MINERAL MIXTURE - AGRAWALLA, J; SETHY, K; BEHERA, K; SWAIN, RK; MISHRA, SK; SAHOO, N; MOHAPATRA, MR; KHADENGA, S (The Indian Journal of Animal Reproduction, 2017)
Recently parturated thirty crossbred cattle were selected for the study from Kakatpur block of Puri district of Odisha. A group of cattle (n=15) were supplemented with specially formulated area specific mineral mixture @ 50 g/animal/day for 90 days, whereas, the remaining (n=15) were kept as unsupplemented controls. An increase (p<0.05) in serum mineral (Ca, P, Zn, Mn, Cu) concentration was observed in supplemented cattle on day 90 in comparison to controls. In brief, the reproductive performance in terms of days to first postpartum estrus, number of services per conception and service period decreased (p<0.05) following mineral supplementation in crossbred cattle.